Taxonomic revision of the Neotropical Myrmicinae ant genus Blepharidatta Wheeler - Brandão, Carlos Roberto F.; Feitosa, Rodrigo M.; Diniz, Jorge L. M. (Zootaxa, 2015)
We revise the taxonomy of the exclusively Neotropical Myrmicinae ant genus Blepharidatta (Attini), redescribing the known species (B. brasiliensis and B. conops), and describing two new species, B. delabiei sp. n. (Brazil: Bahia) and B. fernandezi  sp. n. (Colombia: Amazonas). We also describe worker sting apparatuses, larvae, males, and ergatoid gynes of all species, except for B. fernandezi, known only from few worker specimens; we provide a key for identifying workers, present distribution maps for all species and summarize the knowledge on the biology of Blepharidatta species.